Abnormalities of B-cell activation and immunoregulation in patients with Crohn's disease. Issue 11 (November 1984) - Sieber, G; Herrmann, F; Zeitz, M; Teichmann, H; Rühl, H
Abstract : We have studied B-lymphocyte function in 39 patients with Crohn's disease and 35 normal individuals using a reverse haemolytic plaque assay as the effector system. Ten patients had active Crohn's disease, the others being in an inactive state of the disease. Compared with normal individuals, the Crohn's disease patients - especially those in the active state of the disease - had markedly raised numbers of spontaneous immunoglobulin secreting cells and severely decreased responses to the polyclonal activator pokeweed mitogen. The differences between the reactivity of patients with active disease and those with inactive disease were statistically significant. These findings indicate an in vivo polyclonal B-cell activation in Crohn's disease patients, possibly due to antigen(s) or infectious agent(s). In vitro experiments were performed with separated lymphocytes in order to characterise the mechanism responsible for the altered immune reactivity in Crohn's disease. These revealed an intrinsic B-cell defect as well as an impaired T-helper cell capacity in patients with Crohn's disease. Findings supporting the hypothesis of an increased suppressor activity in Crohn's disease patients could not be observed, and marker analyses revealed normal proportions with the exception of raised Leu 7 positive cells that mediate 'natural killer' and 'killer' cytolysis. We conclude that immune dysfunction in peripheral blood lymphocytes of Crohn's disease patients involves B-cells as well as T-helper cells.